Determinasi Perilaku Pengelolaan Keuangan Mahasiswa Akuntansi DIY: Literasi, Inklusi, Sikap, dan Kontrol Diri - Barbara Gunawan; Muhamad Giffri Maulana (Yayasan Literasi Ilmiah Indonesia, 2026)
Purpose: This study aims to analyze the influence of financial literacy, financial inclusion, financial attitudes, and self-control on the financial management behavior of accounting students in the Special Region of Yogyakarta.Method: In this study, the researcher took a sample of respondents who were active undergraduate accounting students registered at universities in the Special Region of Yogyakarta that had an Accounting Study Program accredited A or